Archives de l’architecture des administrations : un état de la question et de la recherche - Nina Mansion-Prud’homme (In Situ)
This paper seeks to address the topic of 'administrative architecture' with regards to the gathering and the preservation of the sources of their recent history (since 1945). Acknowledging the latest research, this analysis aims to clarifiy the vocabulary used to refer to this architectural theme which is characterised by an interesting contradiction: rather neglected by research, it has the advantage of being documented by very numerous and diverse sources. Like other architectural categories, the history of administrative architectures make use of public archives (from State archives to local archives), and private archives. Among the latest, architects’ archives can be relevant sources to analyse the evolution of architectural programmes, the understanding of construction methods and actors, and forms of architectural languages of these buildings embodying and accomodating power. Conceived in 1986 in the period of “decentralisation” in france, le Centre d’archives d’architecture du xx e siècle of the Institut français d’architecture now has more than 450 architects’ archives. Most of them can enrich the history of architecture of power.